Sustaining Co-operatives: The Role of Board Members and Local Governance in Butwal Sub-Metropolitan City - Poudel, Dadhi Ram; Bashyal, Chiranjibi (Devkota Journal of Interdisciplinary Studies, 2026)
In Nepal, co-operatives have evolved from being just financial entities to becoming lifelines of communities striving for inclusive growth and economic resilience. They especially help people in places such as Butwal Sub-Metropolitan City to come together, pool resources, generate employment and empower women and marginalized groups. But these co-operatives are not easy to keep going. In this study we examine the real dynamics that underpin the sustainability of co-operatives, with particular attention to the roles of board members and local governance. The research is based on in-depth interviews and group discussions with ten selected co-operatives of Butwal. It shows that good leadership, ethical leadership, and supportive policies from local government, make a big difference. When board members are trained, transparent and inclusive, they build trust and ensure stability. Likewise, when local governments actively partner with co-operatives, they help to magnify impact. But poor communication, inadequate training and political interference often get in the way. This suggests investment in leadership development and the formation of genuine partnerships between co-operatives and municipalities can greatly boost the survival and success of these grassroots organizations.